Study of body adiposity index among medical students: a descriptive cross-sectional study - Jha, Reena Kumari; Shah, Bashistha; Mishra, Abadhesh Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Obesity among young people is increasing due to major lifestyle changes, leading to serious health problems. Thus, this study aimed to determine the prevalence of the body adiposity index among medical students at a medical college in Nepal. Method: A descriptive cross-sectional study was conducted in Kathmandu University School of Medical Sciences from August to September 2025 after taking ethical clearance from Institutional Review Committee. Two hundred sixty-eight medical students were enrolled in study using convenience sampling. Body height in meters and hip circumference in centimeters were measured for each participant using measuring tape, and body adiposity Index was calculated as [(hip circumference in cm)/(height in m) 1.5] - 18. Result: Out of 268 participants, 65 (24.3%) had high fat percentage and 47 (17.5%) had very high fat percentage, with mean body adiposity index of 26.18 ± 4.82 and 28.81 ± 2.00, respectively. The mean body adiposity index of males was 23.83 ± 4.88, and that of females was 23.70 ± 7.16. The majority of male participants, 51(38.05%), had high, and 47 (35.03%) had very high body fat percentage; however, majority of female participants, 80 (59.70%), had healthy body fat percentage, and some 14 (10.44%) had high fat percentage. Conclusion: Compared with a previous similar study conducted in Nepal, our study found higher prevalence of very high body fat percentage among medical students. However, majority still had body fat levels within normal or healthy range. Further investigation is needed to identify the factors influencing body adiposity index.